Editorial. - King, Steven (Family & Community History, 2025)
The article discusses the challenges facing higher education in the UK, particularly the humanities, as 104 universities are making staff redundancies and 'rightsizing' their history departments. This trend is attributed to a decline in humanities enrollment, particularly in history, as well as the need for universities to increase productivity to support their science and medicine programs. The editorial highlights the human impact of these cuts, noting that fewer historians will lead to a decrease in scholarly output and early career opportunities. Additionally, it features summaries of three articles related to historical figures and events, emphasizing the ongoing relevance of history despite the sector's struggles.